(untitled) (International Journal of Engineering and Computer Science, 2017)
The paper gives an overview of the meaning of Artificial Intelligence, (AI) Advantages and disadvantages. There are several fields in AI-robotics, speech recognition and expert system-to name a few. Doing the laundry or the dishes may no longer seem a chore. Robots are programmed to perform these activities. The recent times saw the artificially developed robot “Eve” help in searching for new drugs.Eve uses a standardized form of assay to compute Boolean functions of compound properties. These assays can be quickly and cheaply engineered using synthetic biology, enabling more targets to be assayed for a given budget. Another discovery is the anti-cancer drugs which exhibited anti-malarial properties.